DE-ASIGION (DIGITAL PLOTAGON ANIMATION VIDEO) AS A MIDDLE SCIENCE LEARNING MEDIA TO AVOID SDGS 2030 - Mufidah, Alfi; Agustina, Wahyu Laila; Ekapti, Rahmi Faradisya (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
The existence of technological developments accompanied by the demands of the times, requires the quality of education that is effective and efficient for the realization of advanced human resources. Therefore Indonesia plans to implement the Sustainable Development Goals (SDGs) to address education problems. One of the things that can be done is through the development of animated video-based learning media through the plotagon application. The existence of animated video learning media is expected to improve the quality of student learning outcomes. The purpose of this study was to determine the effectiveness of the plotagon animated video learning media on science subjects in junior high school class IX on biotechnology in the food sector. The method used in this research is R&D (Research and Development), which is a method that can produce certain products and is tested for its effectiveness through the development of science learning media in the form of biotechnology animation videos. The results of this study indicate that animated video-based learning media through the plotagon application are preferred by students because they are easy to understand. So it can be concluded that if the animated video of the plotagon is used as a learning medium and applied in the learning process, it can improve the quality of learning outcomes and the quality of education in the future.